Redefining Religious Education
XII, 254 p.
Keywords: This book is a unique collection of interdisciplinary articles that argue for religious education to be directed primarily towards the spiritual insofar as it is part of a flourishing human life. The articles address this issue from the perspectives of theory, different religious traditions and innovative teaching and learning practices.